Service quality and customer satisfaction on two wheelers in Nepal - Shrestha, Mikha (Management Dynamics, 2020)
Service quality is a key to survival for all service providing companies. The modern customer is savvy and technology driven who is demanding better services. With better services companies ensure customer satisfaction which eventually leads to retention of customers. This study accesses to explore the relation between service quality variables and customer satisfaction on two wheelers in Nepal. For this purpose, descriptive cum analytical research design was been adopted. Total 200 Bajaj motorbike owners were taken as a sample. Primary data have been used in the study with the pre structured questionnaires. The findings from correlation matrix showed a significant and positive relationship between service quality and customer satisfaction while comparing dimensions like responsiveness, reliability, assurance, tangibility and empathy. This research resulted in the development of a valid and reliable scale for measuring service quality in the Bajaj two wheelers in Nepal.